DESIGN OF AVAILABLE DATA APPLICATION SYSTEMS INVENT AND OUT OF CHARACTERISTICS IN THE DISTRICT OFFICE. MUARA PINANG, EMPAT LAWANG DISTRICT - Paleska Wulandari (International Journal Cister, 2022)
Archiving is the process of managing or arranging archives by using a certain system so that archives can be found easily and quickly if needed at any time. archives function as memory centers, decision-making aids, evidence of existence and for other purposes. To know the management of archives, the obstacles in processing archives This research method uses the Waterfall method. The waterfall method is serial in nature starting from the planning, analysis, design, and implementation processes on the system.